Deposição de filmes finos de SnO2 e GaAs, visando confecção de dispositivos baseados na heterojunção SnO2/GaAs - Bueno, Cristina de Freitas [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The purpose of this work is the deposition of GaAs thin films through the simple resistive evaporation technique, and SnO2 thin films doped with Eu3+ rare-earth ion, by sol-gel-dip-coating process, combining a semiconductor material with high electron mobility and direct transition (GaAs), with a wide bandgap semiconductor (SnO2), and natural n-type conductivity, where the rare-earth ion emission, including Eu3+, is very efficient. Samples of these two materials are investigated separately, where SnO2:Eu3+ are in the form of thin films or pressed powder into pellets, as well a combined heterostructure. Thus, results for GaAs, SnO2:2%Eu thin films, Eu-doped SnO2 xerogels, and thin films forming the heterostructure GaAs/SnO2:2%Eu are shown and discussed in the this paper. X-ray difraction (XRD) measurements have shown the main crystallographic directios of SnO2 crystals, with identified rutile structure and cassiterite phase, where the estimated crystallite size along the (101) plane has yielded the values 16nm and 19nm, for film deposited on glass and quartz substrates, respectively. Scanning electron microscopy (SEM) images show the surface of heterojunction GaAs/SnO2:2%Eu, presenting an inhomogeneous character with lighter regions, where the energy-dispersive X-ray spectroscopic (EDX) analysis allows obtaining a range of up to 700% variation in the Sn/Eu relative composition in these regions. Protolominescence (PL) measurements enabled the observation of Eu3+ lines, manly to the case of heterostructure samples, and the appearance of a broad band, which shifts to higher energy according to the thermal annealing temperature. Electrical characterization enabled the evaluation of the temperature effect as well saturation by a monochromatic ligh source. Then, it is expected that the study of luminescent mechanisms and electrical behavior help in the production of new devices, such as electroluminescent devices, combining the properties of...

A proposta deste trabalho é a deposição de filmes finos de GaAs através da técnica simples de evaporação resistiva, e de filmes finos de SnO2 dopado com o íon terra-rara Eu3+, pelo processo sol-gel-dip-coating, combinando um material semicondutor com alta mobilidade eletrônica e transição direta (GaAs), com um semicondutor de bandgap largo (SnO2), e condutividade naturalmente do tipo-n, onde a emissão de íons terras-raras, entre eles Eu3+, é bastante eficiente. São investigadas amostras desses dois materiais de forma separada, como filmes finos ou pó de SnO2:Eu3+, pensado na forma de pastilhas, e também combinado como uma heteroestrutura. Assim, são mostrados e discutidos neste trabalho resultados referentes a filmes finos de GaAs, de SnO2:2%Eu, xerogéis de SnO2 dopado com Eu, e de filmes finos formando a heteroestrutura GaAs/SnO2:2%Eu. Medidas de difração de raios-X (DRX) mostraram as principais direções cristalográficas da estrutura cristalina de SnO2, com a estrutura identificada como do tipo rutilo e fase cassiterita, cuja estimativa do tamanho do cristalito para plano (101) forneceu os valores 16nm e 19nm, para filme depositado em substrato de vidro e quartzo, respectivamente. A microscopia eletrônica de varredura (MEV) permitiu observar a superfície da heterojunção GaAs/SnO2:2%Eu, mostrando uma superfície não homogênea, com regiões mais claras, onde a análise de espectroscopia de energia dispersiva de raios-X (EDX) permitiu verificar uma variação de até 700% da composição relativa Sn/Eu nessas regiões. Medidas de fotoluminescência (PL) possibilitaram a observação das linhas de Eu3+, principalmente para o caso de amostras de heteroestruturas, e o aparecimento de uma banda laraga que se desloca para altas energias de acordo com a temperatura de tratamento térmico. A caracterização elétrica realizada possibilitou a investigação tanto do efeito da temperatura como de uma saturação por fonte...
SnO2 and GaAs thin film deposition aiming the construction of devices based on SnO2/GaAs heterojunction
Keywords: Filmes finos; Dioxinas; Estanho; Europio; Fotoluminescencia; Thin films